2017
DOI: 10.15225/pnn.2017.6.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Zespół zmęczenia, depresja oraz jakość życia u pacjentów ze stwardnieniem rozsianym

Abstract: Introduction. Multiple sclerosis is a chronic disease of central nervous system of autoimmunological origin, in which next to an increased physical disability, neuropsychological disorders exist, that lead to significant decrease in patients' quality of life. Aim. The aim of the study was the assessment of prevalence of fatigue syndrome and depression in patients with multiple sclerosis and their influence on functioning in physical, cognitive and psychosocial dimension as well as on the quality of life. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The highest possible score is 63 points. A score of 0–9 points is categorised as no depression, 10–19 points is mild depression, 20–25 points is moderate depression, and 26–63 points is severe depression [ 27 ]. Cronbach’s alpha for the Polish version of BDI_II = 0.93 for healthy people, and 0.95 for people with depressive disorders [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The highest possible score is 63 points. A score of 0–9 points is categorised as no depression, 10–19 points is mild depression, 20–25 points is moderate depression, and 26–63 points is severe depression [ 27 ]. Cronbach’s alpha for the Polish version of BDI_II = 0.93 for healthy people, and 0.95 for people with depressive disorders [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by Król et al among MS patients, sociodemographic variables had no significant relationship with disease acceptance, while a negative relationship was found between duration of illness and acceptance [29]. Studies in a group of people with MS confirmed the presence of varying severity of depressive disorders [30].…”
Section: Discussionmentioning
confidence: 99%